2020
DOI: 10.1371/journal.pone.0236558
|View full text |Cite
|
Sign up to set email alerts
|

How do undergraduates cope with anxiety resulting from active learning practices in introductory biology?

Abstract: Active learning pedagogies decrease failure rates in undergraduate introductory biology courses, but these practices also cause anxiety for some students. Classroom anxiety can impact student learning and has been associated with decreased student retention in the major, but little is known about how students cope with anxiety caused by active learning practices. In this study, we investigated student coping strategies for various types of active learning (clickers, volunteering to answer a question, cold call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 75 publications
(121 reference statements)
1
17
0
Order By: Relevance
“…While we did not test for possible exposure to COVID-19 virus, it is possible that those who perceived as being exposed to virus were more likely to search for information. It is also possible that highly anxious individuals may engage in more information-seeking as an adaptive coping strategy [48]. However, trusting news media was associated with decreased levels of perceptions of bodily dysfunctions.…”
Section: Plos Onementioning
confidence: 99%
“…While we did not test for possible exposure to COVID-19 virus, it is possible that those who perceived as being exposed to virus were more likely to search for information. It is also possible that highly anxious individuals may engage in more information-seeking as an adaptive coping strategy [48]. However, trusting news media was associated with decreased levels of perceptions of bodily dysfunctions.…”
Section: Plos Onementioning
confidence: 99%
“…The benefits of active-learning strategies have been well documented, including increased learning for students, a decrease in the achievement gap for identities historically underrepresented in the sciences, and improved attitudes and perceptions toward science (Armbruster et al, 2009;Haak et al, 2011;Freeman et al, 2014;Theobald et al, 2020). However, recent research has indicated that many active-learning techniques can also increase student anxiety or the perceptions of student anxiety (England et al, 2017;Cooper et al, 2018a;Downing et al, 2020) and that students employ both adaptive and maladaptive strategies to cope with this anxiety (Brigati et al, 2020). Ultimately, students with high anxiety may even learn less in an active-learning classroom (Cohen et al, 2019).…”
Section: Shape Active-learning Strategies To Minimize Anxietymentioning
confidence: 99%
“…, 2018a ; Cooper and Brownell, 2020 ; Downing et al. , 2020 ) and that students employ both adaptive and maladaptive strategies to cope with this anxiety ( Brigati et al. , 2020 ).…”
Section: Building An Empowering Atmosphere In the Classroommentioning
confidence: 99%
“…The benefits of active learning strategies have been well-documented, including increased learning for students, a decrease in the achievement gap for identities historically underrepresented in the sciences, and improved attitudes and perceptions toward science (Armbruster, Patel, Johnson, & Weiss, 2009;Freeman et al, 2014;Haak, HilleRisLambers, Pitre, & Freeman, 2011). However, recent research has indicated that many active learning techniques can also increase student anxiety or the perceptions of student anxiety Cooper, Downing, et al, 2018;Downing, Cooper, Cala, Gin, & Brownell, 2020;England et al, 2017), and that students employ both adaptive and maladaptive strategies to cope with this anxiety (Brigati et al 2020). Some techniques, such as cold-calling -asking a student to share a response with the class without the student volunteering -have been identified as producing particularly high anxiety in students England et al, 2017).…”
Section: Shape Active Learning Strategies To Minimize Anxietymentioning
confidence: 99%